Dynamics of blood cell suspensions in microflows - Viallat, Annie (Boca Raton : CRC Press, 2020)
"Blood microcirculation is essential to our bodies for the successful supply of nutrients, waste removal, oxygen delivery, homeostasis, controlling temperature, wound healing, and active immune surveillance. This book provides a physical introduction to the subject and explores how researchers can successfully describe, understand, and predict behaviours of blood flow and blood cells that are directly linked to these important physiological functions. Using practical examples, this book explains how the key concepts of physics are related to blood microcirculation and underlie the dynamic behavior of red blood cells, leukocytes, and platelets. This interdisciplinary book will be a valuable reference for researchers and graduate students in biomechanics, fluid mechanics, biomedical engineering, biological physics, and medicine. Features: The first book to provide a physical perspective of blood microcirculation Draws attention to the potential of this physical approach for novel applications in medicine Edited by specialists in this field, with chapter contributions from subject area specialists"--
OCLC-licensed vendor bibliographic record.
Keywords: Blood flow; Microcirculation; Blood cells; MEDICAL / Biotechnology; SCIENCE / Physics